Grabbing back : essays against the global land grab - Ross, Alexander Reid (AK Press, 2014)
"Climate change ravages the earth, while wealthy elites try to grab as much of the world's diminishing resources as possible. As Vandana Shiva writes, land is life. But land, and the struggle to possess it, is also power-- colonial and corporate power, to be sure, but also the power of the dispossessed to rise up and call for an end to the global land grab. Grabbing Back maps this struggle, bringing together analysis that uncover the politics of cultivation and control. In this unprecedented collection, on-the-ground activists join forces with critically acclaimed scholars to documents the commodification and consumption of space, from foreclosed homes to annihilated rainforests, from ecotourism in Sri Lanka to the tar sands of Montana, and to outline the strategies and tactics that might halt the destruction"--P. [4] of cover.